Economic and political institutions and entry into formal and informal entrepreneurship - Autio, Erkko; Fu, Kun (Asia Pacific journal of management, 2015)
We investigated the influence of economic and political institutions on the prevalence rate of formal and informal entrepreneurship across 18 countries in the Asia-Pacific region during the period 2001–2010. We found the quality of institutions to exercise a substantial influence on both formal and informal entrepreneurship. One standard-deviation increase in the quality of economic and political institutions could double the rates of formal entrepreneurship and halve the rates of informal entrepreneurship. The two types of institutions had a complementary effect on driving entry into formal entrepreneurship, whereas only direct effects were observed for informal entry.